North American megafauna, friend or foe to woody encroachment across the Great Plains? Further exploring the American bison’s ecological role on plant communities - Noble, Sidney Lake (Kansas State University, 2024)
Across the globe, grasslands are among the most threatened terrestrial ecosystems. Where grasslands remain intact, many face the threat of woody encroachment, which is the spread of woody vegetation into grassland systems. Within North America, woody encroachment causes habitat loss for grassland obligate species, economic loss of rangeland production, and altering the water cycle. The most intact grasslands left in North America are within the Great Plains and face widespread woody encroachment. Another large change in the Great Plains was the removal of large native herbivores, and replacing them with domesticated grazers or removing grazers altogether. Historically, the American Bison numbered between 30-60 million individuals across the Great Plains before their widespread expiration due to European colonization, market forces, and purposeful extermination. Bison reintroduction has become common across the Great Plains for conservation and ranching. This dissertation aims to further disentangle the role of bison on Great Plains’ plant communities in the context of woody encroachment. The effects of bison have been well studied within the mesic grasslands, or tallgrass prairies, of the Great Plains. In tallgrass prairies bison increase plant diversity and compositional heterogeneity. However, bison have been shown to increase woody plants within tallgrass prairie at high fire frequencies by creating low-fuel patches, but little work has been done exploring their effect in the near absence of fire. My second chapter examines the impact of bison on plant communities and woody encroachment in the near absence of fire. I found that bison continue to increase species richness at low fire frequencies, and bison reduce tree cover, especially Juniperus virginiana, one of the most common and impactful encroaching tree species in the Central Great Plains. My third chapter explores whether bison can help or hinder the reversal of encroachment within a woody-dominated state in the Central Great Plains at Konza Prairie Biological Station. Returning frequent fire alone to encroached areas rarely reverses woody encroachment—a pattern known as hysteresis. After three years of annual fire and the establishment of bison exclosures, the woody plant area decreased, but there was no difference between bison presence and exclosures. Tree mortality was higher without bison, and plant community composition remains similar between bison grazed and ungrazed but with higher grass cover in the exclosures. My fourth chapter addresses the impact of bison on plant communities within mixed-grass prairies in the context of woody encroachment, contrasting with the well-documented influences in tallgrass prairies. We find that bison presence in mixed-grass prairies does not markedly increase plant species richness or diversity compared to areas grazed by cattle, in contrast to their effect in tallgrass prairies. Furthermore, bison have little effect on encroached communities. This research suggests that while critical for ecosystem restoration, bison reintroduction exhibits variable outcomes across grassland types, emphasizing the need for site-specific conservation tactics. They highlight the imperative for more expansive research on their ecological impacts beyond the tallgrass prairie, informing future conservation and management decisions as bison reintroduction efforts continue.
Keywords: Bison; Ecology; Grasslands; Plant communities; Alternative states; Woody encroachment